2002
DOI: 10.1063/1.1478138
|View full text |Cite
|
Sign up to set email alerts
|

Functional design of a pulsed two-frequency capacitively coupled plasma in CF4/Ar for SiO2 etching

Abstract: A capacitively coupled plasma (CCP) with a different frequency source at each of two parallel plates is a powerful tool for SiO2 etching. A time modulation of two-frequency CCP by a pulsed-power operation will be one of the practical solutions in the next generation of etchers, and will allow charging-free plasma processes for high-aspect-ratio holes or trench etching. We numerically predict the structure and functions of a pulsed two-frequency CCP in CF4(5%)/Ar, and discuss its ability to generate charge-free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
81
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(83 citation statements)
references
References 41 publications
1
81
0
Order By: Relevance
“…In this paper, we present the simulation results of a two-frequency capacitively coupled plasma (2f-CCP) [13], [14] based on relaxation continuum (RCT) model [15]- [17] with an N -H gas mixture. The plasma and neutrals are simulated self-consistently in the calculation by considering the reactions and transport of both.…”
mentioning
confidence: 99%
“…In this paper, we present the simulation results of a two-frequency capacitively coupled plasma (2f-CCP) [13], [14] based on relaxation continuum (RCT) model [15]- [17] with an N -H gas mixture. The plasma and neutrals are simulated self-consistently in the calculation by considering the reactions and transport of both.…”
mentioning
confidence: 99%
“…Although various research works have been reported in which numerical simulations [9][10][11][12][13][14][15][19][20][21][22][23][24][25][26] and plasma diagnostics [8,28,29,31] were performed to investigate the characteristics of the 2f-CCP etcher, only a few experimental works have been conducted on oxide etching [3,6]. The C 4 F 8 /CH 2 F 2 /O 2 /Ar and C 4 F 6 /CH 2 F 2 /O 2 /Ar mixture gas chemistries have been typically used for SiO 2 contact etching, but no detailed experimental works on the DFS-CCP etching system have been reported [3,6,8,16,18,22,31,36].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in the case where an f LF of less than 2-4 MHz is used, the use of a higher f HF in the generation of the plasma is advantageous in achieving the functional separation of the HF and LF sources, i.e. independent control of the ion flux and energy bombarding the wafer surface [8,[12][13][14]19,20,25,26,31]. Numerical simulations [12][13][14]19,20,25,26] and experiments [8,31] also indicated that a higher ratio of f HF to f LF (f HF /f LF ) is required to retain independent control of the ion flux and energy on the wafer surface in a 2f-CCP etcher when the voltage in the HF power source is increased.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the pulsed plasmas have attracted much attention. [5][6][7][8][9] However, most of these works on pulsed plasmas have been limited only for the discharge driven by the pulsed form of the voltage rather than the current.…”
mentioning
confidence: 99%